Respostas

2014-06-26T12:51:04-03:00
-  o numero -3 e a rais da equação => x = - 3, logo:
x
² - 7x - 2c = 0
(-3)² - 7(-3) - 2c = 0
9 + 21 - 2c = 0
30 - 2c = 0
-2c = -30 (-1)
c = 30/2
c = 15
2 4 2
MUIIIITOOO OBRIGADOOOO!
Por nada.
Corrige ai, 9 + 21 = 30 e nao 12!
OPS....obrigado, vou editar!
Por nada!! ;)
A melhor resposta!
2014-06-26T13:09:25-03:00
Se -3 é a raiz então: x = -3
x² - 7x - 2c = 0
(-3)² - 7 (-3) - 2c = 0
9 + 21 - 2c = 0
30 - 2c = 0
- 2c = 0 - 30
- 2c = - 30 
C = -30 / -2
C = 15
1 5 1